Review of The Snake and the Mongoose: The Emergence of Identity in Early Indian Religion. By Nathan McGovern - Lubin, Timothy (JAOS, 2024)
The Snake and the Mongoose: The Emergence of Identity in Early Indian Religion. By Nathan McGovern. New York: Oxford University Press, 2019. Pp. xi + 313. $105.